The Influence of Particle size and Guluronic/Mannuronic Proportion of Alginate on Physical and Sensory Characteristics of Restructured Products from Soursop - Sri Raharjo; Zaki Utama (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2003)
The application of restructuring technology is intended to add value for local fruits. Fresh and ripe sour sop fruits are frequently of having defective appearance, irregular shape and size, or showing signs of insect infestation which make the whole fruit is less acceptable by consumers. Previous study has indicated that sour sop fruit can be restructured into a fresh fruit product with acceptable sensory characteristics using calcium alginate gel system. This particular study was intended to determine the effect of alginate powder particles size and its guluronic/mannuronic proportion on the physical and sensorial properties of restructured sour sop. The restructured fruit product was evaluated based on its gel strength, pH colour, and sensory attributes which include taste, aroma, mouth feel, appearance, and hardness. Sour sop restructured by internal setting with coarse alginate powder (36 mesh) tend to have softer gel compared to the use of fine alginate powder (120 mesh). Different proportion of guluronic/mannuronic in the alginate used for the restructurization resulted in the same gel strength when calcium lactate powder was used. However, the use of encapsulated calcium lactate resulted in stronger gel with alginate containing higher proportion of mannuronic acid. The alginate particle size and proportion of guluronic/mannuronic content showed no significant difference in product colour and sensory attributes evaluated. Key words : Alginate, sour sop fruit, restructurization.